Plasma clozapine and norclozapine in relation to prescribed dose and other factors in patients aged <18 years: data from a therapeutic drug monitoring service, 1994–2010. Issue 2 (3rd July 2012) - Couchman, Lewis; Bowskill, Sally V.J.; Handley, Simon; Patel, Maxine X.; Flanagan, Robert J.
Abstract Aim Clozapine is used in children and adolescents to treat early onset schizophrenia, but data on efficacy and on the plasma clozapine concentrations attained are limited. Methods We studied data from a clozapine therapeutic drug monitoring (TDM) service, patients in the UK and Eire aged <18 years, 1994–2010. Multiple linear regression analysis was performed to investigate the relationship between plasma clozapine concentration and dose, age, sex, body weight, plasma clozapine:norclozapine ratio (clozapine metabolic ratio (MR)) and smoking habit. Results There were 1408 samples from 454 patients, 267 (59%) males aged at time of first sample (median = 17; range = 8–17 years) and 187 (41%) females aged 16 (10–17) years. The plasma clozapine concentration was <0.35 mg L−1 in 36%, and ≥0.60 mg L−1 in 31% of samples (6.4% samples ≥1.0 mg L−1). Although plasma clozapine was broadly related to prescribed dose, there was much variation: 10% of samples had plasma clozapine >0.60 mg L−1 at prescribed clozapine doses of 50–150 mg d−1 (66% <0.35 mg L−1), while 12% of samples had plasma clozapine <0.35 mg L−1 at doses ≥650 mg d−1 (62% >0.6 mg L−1). The covariates studied in the 16–17‐year‐olds had proportionately similar influences to those observed in adults. Together they explained 48% of the variance observed in plasma clozapine, with dose, smoking habit, MR and sex being major influences. In the younger patients, there were very few smokers, and the influence of sex did not reach statistical significance. Conclusions As in adults, clozapine TDM may help in assessing adherence and in dose adjustment, for example if smoking habit changes.